Meningkatkan Hasil Belajar Siswa Kelas IV Melalui Penerapan Model Kooperatif Tipe Picture And Picture Pada Materi Metamorposis - Lestari, Destiani Fuji; Sidik, Geri Syahril; Maftuh, Ade (CV. Generasi Insan Rafflesia, 2024)
This research the issue of low student performance in science. Specifically on the topic of metamorphosis, as indicated by test results. The average science scores of Glade IV student remain below the desired standards. At SD Negeri 3 Cibalong, for instance, results from a recent test show that out of 29 students, only 14 (or 48%) achieved scores above the Mininum Completeness Criteria (KKM) , while 15 students (or 52%) scored below, it with an average score or 50.4 against the KKM benchmark of 70. To address this, classroom action research (PTK) was conducted in two cycles to measure significant progress. In the first cycle, the learning outcomes improved to 90,62%. Due to a more engaging and dynamic learning approach, the second cycle saw further improvement, reaching 93,75% and increase of 3,13% teacher activity in managing the learning process also showed growth, with an increase from 89, 28% in the first cycle, despite some obstacles, to 93,10% in the second cycle, marking a gain of 4, 18%.